ENANTIOSPECIFIC SYNTHESES OF INTERMEDIATES IN THE TOTAL SYNTHESIS OF PSEUDOMONIC ACIDS - Fleet, G; Gough, M (1982)
Enantiospecific syntheses of 1S,6S-3,7-dioxabicyclo[4.3.0]non-4-en-8-one (1) and of the enantiomer (2) from D- and L-arabinose respectively have been achieved by two different routes. The conversion of (1) to 6S-(3R-acetanilido)-3,6-dihydro-2H-pyranyl-N,N-dimethylacetamide (3), a key intermediate in the synthesis of pseudomonic acids, is described. © 1982.